Foundations of Islamic economics - Mohamed Haneef, Mohamed Aslam; Mohd. Arshad, Mohd. Nahar; Mohammed, Mustafa Omar (International Institute of Islamic Thought-IIUM, 2023)
The textbook "Foundation of Islamic Economics" provides a comprehensive introduction to the principles and concepts of Islamic economics. The book is divided into 6 chapters, each focusing on different aspects of the subject. Chapter 1 explores the relationship between Islam, its worldview, and economics. Chapter 2 examines the methodology of Islamic economics, including sources of knowledge and the process of developing Islamic economic theory. Chapter 3 covers the characteristics of an Islamic economic system, including its philosophical foundations, property ownership and decision-making processes. Chapter 4 looks at how resources are allocated in the Islamic economic system, with a focus on efficiency and fairness. Chapter 5 examines the principles and methods of distribution in the Islamic economic system, with a focus on income distribution and social welfare. Chapter 6 covers various topics related to Islamic financing, including the issue of ribs and Islamic contracts used in Islamic finance.